197k views
5 votes
H(x+1)=x^2-4 evaluate function by substuting x+1

User Gradbot
by
5.4k points

2 Answers

1 vote

Answer:

h(x + 1) = (x+3)(x-1)

Explanation:

Simply plug the value of x+1 into the equation for x.

h(x) = x^2 - 4

h(x + 1) = (x + 1)^2 - 4

h(x + 1) = x^2 + 2x + 1 - 4

h(x + 1) = x^2 + 2x - 3

h(x + 1) = (x+3)(x-1)

Cheers.

User Dane Jordan
by
4.6k points
3 votes

Answer:

h(t)= t² - 2t -3

Explanation:

h(x+1)= x²-4 is the given function

We can write it x²-4 as:

  • (x+2)(x-2)= (x+1+1)(x+1 - 3)

Substituting x+1 with t. Then function is:

  • h(t)= (t+1)(t-3)= t² - 2t -3

or

  • h(t)= t² - 2t -3
User Anil Koppula
by
4.9k points